Strategi Perusahaan Kosmetik Korea Untuk Memperkuat Marketing Di Indonesia - Lee, Jweyoung; Premananto, Gancar Candra (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2022)
Assessment of beauty in other countries is very different, this shows that beauty is something that is very relative and cannot be measured. Several factors cause the construction of beauty in each area to be different, one of which is the cultural factor. It is undeniable, in the current era of globalization, industrial development is growing rapidly in countries around the world. Beauty is very important for Korean society, especially women. This is the basis why cosmetics are the primary needs of society and the demand for cosmetics in the market continues to increase from year to year. In the case of Korea, the number of Muslim tourists is increasing year by year, and their Korean cosmetic purchases are also increasing rapidly. In this study, the author uses a qualitative method by means of structured interviews regarding the use and interest in cosmetic products originating from Korea by explaining several reference questions, including: This study tries to suggest a more successful entry strategy for Korean cosmetic companies in the Indonesian cosmetic market. However, although a successful entry strategy in this study can explain the Indonesian cosmetic market, it is difficult to explain it as a successful entry strategy into other Southeast Asian countries or Islamic cultural markets. Keywords: Cosmetics; Marketing; Strategy